HUKUM KELUARGA DI KUWAIT: STUDI WASIAT WAJIBAH - Kamal, Helmi (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2013)
There is a number of family law reform carried out in a number of countries, including the one country in the Middle East (West Asia), namely Kuwait. Kuwait against British protectorate status ended since independence on June 19, 1961. Then the constitution was enacted in 1962 (Basic Law / Constitution) states that made shariah (Islamic) law as the basis in Kuwait. The Constitution declared Islam as the state religion and sharia as the main source of law. The Constitution further states,